2010
DOI: 10.3155/1047-3289.60.2.237
|View full text |Cite
|
Sign up to set email alerts
|

Aerosols Emitted in Underground Mine Air by Diesel Engine Fueled with Biodiesel

Abstract: Using biodiesel in place of petroleum diesel is considered by several underground metal and nonmetal mine operators to be a viable strategy for reducing the exposure of miners to diesel particulate matter. This study was conducted in an underground experimental mine to evaluate the effects of soy methyl ester biodiesel on the concentrations and size distributions of diesel aerosols and nitric oxides in mine air. The objective was to compare the effects of neat and blended biodiesel fuels with those of ultralow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 18 publications
5
58
3
Order By: Relevance
“…(12,17,18,25) However, other studies have shown an increase in NO 2 or reductions in CO biodiesel emission concentrations compared to diesel fuel. (15,25) Our findings are also inconsistent with prior studies showing increased aldehyde concentrations with biodiesel use. (12,18) However, neither of the engines used in these studies used a DOC as was done in our study.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…(12,17,18,25) However, other studies have shown an increase in NO 2 or reductions in CO biodiesel emission concentrations compared to diesel fuel. (15,25) Our findings are also inconsistent with prior studies showing increased aldehyde concentrations with biodiesel use. (12,18) However, neither of the engines used in these studies used a DOC as was done in our study.…”
Section: Discussioncontrasting
confidence: 65%
“…(25) Our research revealed increasing tOC and decreasing tEC concentrations associated with B75 use, consistent with previously published studies. (15,17,22,25,26) These studies used a variety of biodiesel blends, pollution control devices (or lack thereof), loading procedures, and engine configurations, all of which can influence vehicle emissions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This requires a multipollutant/multieffect air quality management strategy (Chow et al, 2010;Chow and Watson, 2011;Hidy et al, 2011;Hidy and Pennell, 2010). Transportation biofuels may reduce CO 2 emissions over their life cycles (Agusdinata et al, 2011;Hossain and Davies, 2010;Hsu et al, 2010;Meyer et al, 2011;Ou et al, 2010;Yan et al, 2010;Yu and Tao, 2009;Zhai et al, 2009), but they may result in increased gaseous and particulate pollutant emissions (Betha and Balasubramanian, 2011;Bugarski et al, 2010;Di et al, 2009; Guarieiro et al, 2009;Liu et al, 2009;Yanowitz and McCormick, 2009). Some of these emission rates may be small when engines are certified, but emission controls deteriorate over time; the more complex the after treatment, the greater is the potential for deterioration.…”
Section: Eti In Advanced Transportationmentioning
confidence: 99%